Sodium glucose cotransporter SGLT1 as a therapeutic target in diabetes mellitus. (1st September 2016) - Song, Panai; Onishi, Akira; Koepsell, Hermann; Vallon, Volker
ABSTRACT: Introduction : Glycemic control is important in diabetes mellitus to minimize the progression of the disease and the risk of potentially devastating complications. Inhibition of the sodium–glucose cotransporter SGLT2 induces glucosuria and has been established as a new anti-hyperglycemic strategy. SGLT1 plays a distinct and complementing role to SGLT2 in glucose homeostasis and, therefore, SGLT1 inhibition may also have therapeutic potential. Areas covered : This review focuses on the physiology of SGLT1 in the small intestine and kidney and its pathophysiological role in diabetes. The therapeutic potential of SGLT1 inhibition, alone as well as in combination with SGLT2 inhibition, for anti-hyperglycemic therapy are discussed. Additionally, this review considers the effects on other SGLT1-expressing organs like the heart. Expert opinion : SGLT1 inhibition improves glucose homeostasis by reducing dietary glucose absorption in the intestine and by increasing the release of gastrointestinal incretins like glucagon-like peptide-1. SGLT1 inhibition has a small glucosuric effect in the normal kidney and this effect is increased in diabetes and during inhibition of SGLT2, which deliver more glucose to SGLT1 in late proximal tubule. In short-term studies, inhibition of SGLT1 and combined SGLT1/SGLT2 inhibition appeared to be safe. More data is needed on long-term safety and cardiovascular consequences of SGLT1 inhibition.